Diplopia: A Rare Manifestation of Neuroborreliosis - Ayushi Dixit; Yesika Garcia; Lauren Tesoriero; Charles Berman; Vincent Rizzo (Case Reports in Neurological Medicine)
Early disseminated Lyme disease typically presents with cardiac, rheumatologic, or neurologic symptoms. Though uncommon, Borrelia burgdorferi can invade the central nervous system and cause neuroborreliosis. In these patients, facial palsy, headache, and stiffness of the neck are the most common presenting symptoms. Our case describes a patient with oculomotor nerve palsy manifesting as double vision as the initial presentation of neuroborreliosis.